PERBANDINGAN METODE (Normalized Difference Built-Up Index) NDBI DAN (Tasseled Cap Transformation) TCT DALAM MENENTUKAN LAHAN TERBANGUN STUDI KASUS DKI JAKARTA - Abiyoga Hartyas Ghifari, - (2019)
Build land is important for urban areas. The city of Jakarta is one of the developing cities in the development. Development undertaken to meet the needs of the community, but the development undertaken should pay attention to good urban governance so that the quality of life of society is maintained and there is harmony between natural and artificial environment. Build land becomes an important issue so the government supports it by issuing PERPRES No. 54 of 2008. It takes a system capable of monitoring the evelopment of land use by utilizing Geographic Information System analysis. This study uses NDBI (Normalized Difference Built-Up Index) and TCT (Tasseled Cap Transformation) transformations to detect the existing wake land in the city of Jakarta and as a comparison method to detect the built-up land. Level of accuracy of transformation in each transformation is different for TCT has overall accuracy value equal to 71,33% while kappa equal to 41,17%, while for NDBI level accuracy equal to 88,09% and kappa equal to 74,5%. Based on the above results obtained the area of land constructed city of Jakarta in 2017 is 53.04%